The Effect of Fertility Hormones Levels on Osteoporosis Infection of Basra Women - Seiwan, Anwar Nather; AL. Ibraheem, Shrouk Abdulrazak Hassan (American Journal of Biomedicine and Pharmacy, 2025)
Background: Osteoporosis is the most not unusual stop-degree in postmenopausal ladies characterised by using extensive reduction in bone mass and improvement of osteoporosis. Measurement of bone mass within the backbone Trendy is a reliable degree of bone density and may consequently predict fracture chance Dual-power X-ray absorption size (DXA) is an accurate non-invasive system measuring bone density, with reduced comparison for mistakes and no confusion with the biochemical boundaries of the two factors to locate of the proposed blended mediators. Methods: The study, set in 2024 in a private laboratory in Basra, southern of Iraq, had 100 participants, including 50 individuals diagnosed with osteoporosis and 50 controls apparently healthy, the age ranged from 20 to 60 years . Results: Limits of calcium, early morning planetary vision, alkaline phosphatase, nutrient source D, and magnesium blur significant differences between 'two combined groups (P-value > 0.05). In the control institution, the relationship between salty phosphatase and cartilage mineral content material (BMC) and thin field (BA) within the spine changed into great accompanying a equivalence cooperative of − 0.402 and 0.258, respectively (P-income < 0.05) and BMD and T-rating in the femoral narrow connector quantity confirmed a right away and essential friendship accompanying phosphorus (equivalence = 0.368; P worth = 0.038). There changed into a significant relationship betwixt the Z-rating accompanying calcium (equating = 0.358; P cost = 0.044).Assessing Estradiol level in women result are given in picograms in keeping with milliliter(pg/ml). Normal degress fo cinsudered r estradiol are30_400pg/ml for postmenopausal women. And assessing progesterone levels in women, progesterone tiers had been measured in nanograms according to milliter(ng/ml) the chart under shows what is considered to be aordinary progesterone degree for an grownup lady at distinctive ranges of menstruation and being pregnanat, follicular stage of the menstrual cycle<0.7,luteak stage of the menstrual cycle 2_25,first trimester of pregnancy 10_44,second trimester of pregnancy 19.5to 82.5and third trimester of pregnancy 65_290 Statistical analysis showed that osteoporosis was significantly associated with old age, specifically in females, with a p-value of <0.05 bearing statistical significance. Furthermore, BMI has an inverse relationship with BMD, while people living a sedentary life exhibited a greater risk for osteoporosis. These findings highlight the need for early screening and preventive programs for these high-risk groups. The statistical evidence highlights the need for community-level health programs toward education, nutrition, and physical activity to reduce osteoporosis burden. Conclusion: In the studied population, osteoporosis occurs commonly and severely and is linked with a variety of risk factors including age, sex, and lifestyle modifications.